The Interconnection of Tambakrejo Community's Lifestyle with Heavy Metal Content in Green Mussels (Perna viridis) along the North Coast of Semarang - Niswatus Shabrina; Ahmad Fauzan Hidayatullah (UIN Sulthan Thaha Saifuddin Jambi, 2023)
With the current environmental conditions in the Tambakrejo community, there is a strong interconnection between the levels of heavy metal content in green mussels found in river estuaries and the northern coast of Semarang. The heavy metal content of iron (Fe) in water, sediment, and green mussels (Perna viridis) in the waters of Tanjung Emas, Semarang has been studied in the Journal of Tropical Marine Sciences. These points of contamination result in an interconnection between the lifestyle of the Tambakrejo residents and the heavy metal content in the green mussels consumed by the community. The heavy metal content of Fe in sediments was found to be higher than that in water samples at all stations. The heavy metal content of Lead (Pb) and Chromium (Cr) in green mussels (Perna viridis) in the waters of Morosari, Sayung, Demak Regency was also studied. Tambakrejo is a village chosen as a representative village to investigate the relationship between the community's lifestyle and the heavy metal content present in green mussels along the northern coast of Tanjung Emas, Semarang.